Mentoring and Coaching as a Learning Technique in Higher Education: The Impact of Learning Context on Student Engagement in Online Learning - Kelum A. A. Gamage; D. A. Sharmini Perera; M. A. Dilini N. Wijewardena (MDPI AG, 2021)
Coaching and mentoring has been regarded as one of the key learning techniques in the modern learning environment in the recent past. With the swift shift in the higher education sector to a more digitally driven learning environment, limited research has evaluated the impact of coaching and mentoring on student engagement in online learning. This study aimed to evaluate the impact of coaching and mentoring on enhancing student engagement in the higher education sector. The study applied a combination of quantitative and qualitative methods of data collection, where the primary data were collected from 120 respondents via a questionnaire and 20 in-depth interviews, covering undergraduates through a simple random sampling technique. The data analysis showed that the mentor's ability to facilitate learning and encourage mentees to be focused on their goals were the most significant factors that affected student engagement in online learning. In total, 43% of the respondents extremely agreed that they are willing to recommend their colleagues to receive the service of a mentor to help them reach their optimum potential in an online learning environment. The findings of the study recommend that the higher educational institutes should administer a sound mentoring process that meets the ethical backgrounds to consistently support the continuous improvement of the students in an online learning environment to enhance their engagement in learning activities.